Serum total IgE may be a biomarker among chronic pulmonary aspergillosis patients with elevated serum total IgE levels: A cohort study with pathological evaluations. (31st January 2022) - Watanabe, Shizuka; Suzuki, Junko; Suzukawa, Maho; Takeda, Keita; Imoto, Sahoko; Kitani, Masashi; Fukami, Takeshi; Sasaki, Yuka; Hebisawa, Akira; Matsui, Hirotoshi
Abstract: High serum total immunoglobulin E (IgE) levels have been reported in chronic pulmonary aspergillosis (CPA). However, researchers have not verified if they reflect the disease activity. We aimed to compare the serum total IgE levels in CPA cases with high serum IgE during an exacerbation or when stable and examined the IgE expression patterns in the lesions via immunofluorescence staining. From April 2016 to September 2019, we extracted CPA cases with elevated serum total IgE levels based on the criteria of the Infectious Diseases Society of America. We retrospectively analyzed serum total IgE levels and other parameters and eventually extracted 32 cases. The patients' serum total IgE levels were significantly higher in the exacerbation period than in the stable period ( P  < .0001). The median rate of change was 1.76 times (quartile 1.41–3.25). In addition, we used surgical specimens of CPA cases with high serum total IgE levels, normal serum total IgE CPA cases, and control surgical specimens and performed immunofluorescence staining with IgE, mast cell tryptase, CD138, and 4, 6-diamidino-2-phenylindole. We observed multiple mast cells and plasma cells in the CPA cases regardless of the serum total IgE level. In contrast, multiple IgE-positive cells co-stained with tryptase were observed in CPA cases with high serum total IgE levels. This finding suggested that serum total IgE could serve as a biomarker for evaluating disease severity. Immunofluorescence staining suggested that IgE may play a role in pathogenesis through activation of mast cells by cross-linking in cases of CPA with high serum total IgE levels. Lay summary: High serum total IgE levels are common in chronic pulmonary aspergillosis. This novel study indicated that serum total IgE is a possible biomarker of the disease activity in the aforementioned condition. Immunofluorescence staining indicated a possible role of IgE in disease pathogenesis.